Estimation of the time delay of hydroacoustic signals for passive location of underwater objects - Makar, A. (Archives of Acoustics, 2004)
In this paper a method of time delay estimation of acoustic signals radiated in water has been shown. The source of these signals is a moving ship. The gradient adaptive method of minimizing the error has been used. An algorithm of estimation using this method and the results of estimation the real signals radiated by a moving ship have been presented.